2023
DOI: 10.1186/s12943-023-01841-8
|View full text |Cite
|
Sign up to set email alerts
|

m6A-regulated tumor glycolysis: new advances in epigenetics and metabolism

Abstract: Glycolytic reprogramming is one of the most important features of cancer and plays an integral role in the progression of cancer. In cancer cells, changes in glucose metabolism meet the needs of self-proliferation, angiogenesis and lymphangiogenesis, metastasis, and also affect the immune escape, prognosis evaluation and therapeutic effect of cancer. The n6-methyladenosine (m6A) modification of RNA is widespread in eukaryotic cells. Dynamic and reversible m6A modifications are widely involved in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 209 publications
0
9
0
Order By: Relevance
“…As an epitranscriptomic modification, the m6A modification of RNA is widely involved in the regulation of cell renewal and differentiation and metabolism during the progression of various inflammatory and cancerous diseases. 38 However, the specific mechanism by which m6A modification mediates mitochondrial dysfunction under hypoxic gastric condition is still unknown. Therefore, MeRIP‐seq analysis of normal and PHT‐induced gastric mucosa tissues revealed that m6A modification plays an important role in gastric mucosal lesions in PHT.…”
Section: Discussionmentioning
confidence: 99%
“…As an epitranscriptomic modification, the m6A modification of RNA is widely involved in the regulation of cell renewal and differentiation and metabolism during the progression of various inflammatory and cancerous diseases. 38 However, the specific mechanism by which m6A modification mediates mitochondrial dysfunction under hypoxic gastric condition is still unknown. Therefore, MeRIP‐seq analysis of normal and PHT‐induced gastric mucosa tissues revealed that m6A modification plays an important role in gastric mucosal lesions in PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Not a few excellent studies have discussed the regulatory roles of RNA modifications on metabolism in specified pathological situations, with a particular focus on cancers. 10 12 However, there is a deficiency of a comprehensive and wide-scale review on the epigenetic-metabolic interaction covering health and disease context.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased tumor glycolysis and decreased extracellular pH impede immune cell-mediated targeting of cancer and other therapeutic approaches . Glycolysis levels have been recognized as a criterion for assessing the efficacy of cancer drug therapies. , Therefore, evaluating glycolysis is crucial in predicting chemotherapeutic resistance and monitoring treatment outcomes in cancer therapy …”
Section: Introductionmentioning
confidence: 99%
“…2,8−12 Therefore, evaluating glycolysis is crucial in predicting chemotherapeutic resistance and monitoring treatment outcomes in cancer therapy. 13 Currently, biochemistry analyzers and assay kits have been developed to measure extracellular acidification rate and lactate production. 14,15 However, these methods are primarily applicable at the cellular level or in isolated tissue detection.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation